Studi Eksplorasi Penggunaan Kondom pada Pekerja Seks Komersil (PSK) Langsung di Daerah Sanur - Luh Gede Pradnyawati (Politeknik Kesehatan Kartini Bali, 2022)
Previous research on Commercial Sex Workers (CSWs) found that 250 CSWs in Denpasar and surrounding areas, around 14% were infected with HIV/AIDS. South Denpasar District is the sub-district with the most STI cases, namely in the Sanur area. According to data from the Denpasar City Health Office in 2017, there were 450 direct sex workers in the Sanur area. It appears that problem of STIs among sex workers directly in the Sanur area is quite high. Therefore, it is necessary to conduct an exploratory study to dig deeper into the use of condoms in direct sex workers in the Sanur area. This study uses a qualitative method with purposive sampling technique on 15 informants consisting of direct sex workers, pimps and customers by conducting in-depth interviews. The results showed that although the use of condoms had been encouraged, there were also participants who did not use condoms when dealing with customers. The mostly reasoned that their partners did not like the use of condoms in sexual intercourse. The low use of condoms is related to economic factors. If you use a condom in sexual intercourse, it will reduce the income of the prostitutes directly.